Subglacial sediment pathways and deglacial chronology of the northern Barents Sea Ice Sheet. (10th May 2017) - Hogan, Kelly A.; Dowdeswell, Julian A.; Hillenbrand, Claus‐Dieter; Ehrmann, Werner; Noormets, Riko; Wacker, Lukas
Abstract : New information is presented on the configuration of the northern Barents Sea Ice Sheet (BSIS) during the last glacial and deglaciation (21–11.5 ka). The glacial dynamics of the BSIS that we discuss are based on clay‐mineral compositions of subglacial tills and a distinct kaolinite source in the central Barents Sea where previous workers have placed a large, single ice dome for the last glacial BSIS. Our results, which appear to show that subglacial sediments were sourced locally, suggest that the BSIS consisted at least temporarily of multiple domes and may have been more dynamic than previously thought. New radiocarbon dates are presented along with new ice‐extent reconstructions for 16.5–15, 14, 13.5 and 11.5 ka. Our reconstructions add information to previous regional and continental‐scale efforts in areas east of Svalbard. Ice retreat in the northern Barents Sea progressed as follows. (i) 19–16.5 ka. Major calving led to dynamic thinning in shelf troughs and was accompanied by significant ice‐sheet thinning inland as a result of ice drawdown. (ii) 16.5–15 ka. Rapid ice‐margin retreat of between 75–100 km occurred, via lift‐off and iceberg calving, in Hinlopen and Kvitøya troughs, as well as major retreat (>300 km) in Franz Victoria Trough (FVT) further east. (iii) 15–13.5 ka. Retreat progressed westwards from the FVT towards Svalbard with troughs east of Svalbard (Kvitøya, Olga, and Erik Eriksen) mostly ice‐free by 13.5 ka. (iv) 13.5–11.5 ka. Ice retreated gradually towards residual ice masses on Svalbard, Kong Karls Land and possibly Storbanken. Our data require a modification of earlier views of the BSIS because they point toward a more dynamic ice sheet and decay that, once initiated at the shelf break, was dominated by the withdrawal of ice from the FVT that progressed westwards towards the Svalbard archipelago.